Political Value of Contracts of the Russian Federation with the States of South Caucasus and their Influence on Regional Policy - Ekaterina Sergeyevna Andreeva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article investigates the influence of international military treaties on regional policy. Military contracts are considered as part of the implementation of the state’s military policy. It assesses the role of the military contracts to provide security. The article presents a classification of military contracts, the influence of the military agreements of the Russian Federation on the political situation in the South Caucasus.